The Effect of Ginger-chamomile Sachet with Honey on Primary Dysmenorrhea and Associated Symptoms: A Randomized, Double-Blind, Controlled Trial - Shabani, Fatemeh; Chabra, Aroona; Vakilian, Katayon; Bioos, Soodabeh; Bozorgi, Mahbubeh; Ayati, Mohammad H.; Nejatbakhsh, Fatemeh (Current Women's Health Reviews, 2020)
Background: Dysmenorrhea is one of the most frequent pelvic pains among young women, impairing their quality of life. Objective: This research aims to investigate the effect of ginger-chamomile herbs with honey in reducing dysmenorrhea pain, associated symptoms, and the extent of bleeding. Methods: In this randomized clinical trial (IRCT No.: 2016100825031N5), 200 female students with primary dysmenorrhea, from Arak universities, were included and randomly divided into two groups. All the students were evaluated for one cycle without intervention, then group (A) received mefenamic acid (250 mg) and group (B) received ginger (1000 mg), chamomile (5000 mg), and one teaspoonful of honey for two days before and for the first three days of menstruation, three times a day, in two consecutive cycles. Pain severity, associated symptoms of dysmenorrhea, and bleeding were assessed using a visual analogue scale, Andersch-Milsom Verbal Scale, and Higham chart. Data were analyzed by descriptive and inferential statistical tests through SPSS21. Results: The pain intensity in group B diminished significantly after the intervention in comparison to group A (p <0.05). The mean severity of dysmenorrhea accompanying symptoms decreased significantly in group B compared to group A (P=0.009). However, the mean quantity of bleeding significantly decreased in group A (P = 0.004), with no increase in the extent of bleeding in group B. Conclusion: The present study indicated that the combination of the ginger-chamomile sachet with honey has the same effect as nonsteroidal anti-inflammatory drugs for pain mitigation, and the associated symptoms reduced better than mefenamic acid.
Keywords: dysmenorrhea